1962
DOI: 10.1063/1.1733003
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Sublimation of Ammonium Halides

Abstract: The rates of sublimation of ammonium chloride, bromide, iodide, and fluoride have been determined by two different experimental techniques over the temperature range of 100° to 600°C, corresponding to an increase in sublimation rate of 104. The two experimental methods employed were the isothermal rate of weight loss using a quartz spring balance, and the hot-plate linear pyrolysis method. The low activation energy (about one-third the heat of sublimation) found for ammonium chloride by earlier investigators h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…It is well known that NH 4 Cl undergoes sublimation at 338 1C according to NH 4 Cl (s) -NH 3 þHCl. We observed the complete elimination of the NH 4 Cl at 425 1C, which is consistent with Chaiken et al [25] who found that the typical sublimation weight loss of NH 4 Cl is over 90% when heated for E60 min at elevated temperatures. A slow ramp rate was employed here to ensure the gradual sublimation of NH 4 Cl and the release of HCl, which reacts at the surface of the SnO 2 NWs giving SnCl 4 , according to SnO 2 þ4HCl-SnCl 4 þ2H 2 O .…”
Section: Resultssupporting
confidence: 92%
“…It is well known that NH 4 Cl undergoes sublimation at 338 1C according to NH 4 Cl (s) -NH 3 þHCl. We observed the complete elimination of the NH 4 Cl at 425 1C, which is consistent with Chaiken et al [25] who found that the typical sublimation weight loss of NH 4 Cl is over 90% when heated for E60 min at elevated temperatures. A slow ramp rate was employed here to ensure the gradual sublimation of NH 4 Cl and the release of HCl, which reacts at the surface of the SnO 2 NWs giving SnCl 4 , according to SnO 2 þ4HCl-SnCl 4 þ2H 2 O .…”
Section: Resultssupporting
confidence: 92%
“…[ 29 ] the sublimation rate of NH 4 Cl increases by a factor of 10 4 when changing the temperature from T = 100 to 600 °C and the typical sublimation weight loss of NH 4 Cl is over 90% when heated for ≈60 min. It is interesting to point out here that this sublimation process is endothermic and the temperature is expected to be reduced only by a few tens °C in the case of NH 4 Cl [ 29 ]. The decomposition of NH 4 Cl enhances the porosity of the Sn melt and more importantly acts as a dispersant increasing the amount of Sn that is transferred into the gas stream.…”
Section: Resultsmentioning
confidence: 99%
“…4 " 6 Similar experimental configurations have been employed in much earlier work on linear pyrolysis of vaporizable or decomposable materials, in which steady regression rates were measured when the material was pressed against a heated, impermeable flat plate. 7 The potential importance of compressibility in such experiments has been pointed out by Cantrell, 8 who had earlier 9 completed an analysis of such flows including compressibility effects but not considering the simplifications that arise in the limit of large Reynolds numbers, addressed herein.…”
Section: Introductionmentioning
confidence: 99%